A PEDOT:PSS functionalized capacitive sensor for humidity. (August 2020) - Yao, Xuesong; Cui, Yue
Highlights: The work reports a PEDOT:PSS functionalized capacitive sensor for humidity. The sensor is constructed by fabricating an interdigital capacitor and coating PEDOT:PSS on it. The sensor exhibits a sensitive and linear detection range with a short measuring time for humidity. Abstract: The development of new sensing configurations could open up exciting opportunities for various applications, such as healthcare and environmental monitoring. Humidity is an important parameter that indicates the air situation. Capacitive configurations have recently attracted great attentions as novel electronic devices for sensing. PEDOT:PSS is a sensitive polymer whose performance can be affected by humidity. Here, for the first time, we demonstrate a PEDOT:PSS functionalized capacitive interdigital electrode for the detection of humidity. While the humidity changes, the electrical property of PEDOT:PSS changes, resulting in a capacitive response of the sensor. The capacitive humidity sensor shows a linear detection range with a short response time. We anticipate the work can provide new platforms for the fundamental studies of new electronic devices in sensing, and advance related applications in healthcare and environment.